2013
DOI: 10.1016/j.rboe.2013.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Open tibial shaft fractures. Treatment with intramedullary nailing after provisional stabilization with non penetrating external fixator

Abstract: Objective To evaluate the incidence of union, nonunion, deep infection and factors influencing the time of bone healing in the treatment of open tibial shaft fractures Gustilo and Anderson types I and II initially treated with a non penetrating external fixator (Pinless ® ) followed by an unreamed intramedullary locked nail (UTN ® ). Methods It is a prospective study of 39 open tibial shaft fractures. According to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
(95 reference statements)
1
3
0
2
Order By: Relevance
“…The tibia and the fibula bones were the most frequently involved in open fractures making up about 45% of cases in this series. Several previous studies also reported similar findings [9, 16, 20, 21]. The reason for this observation has been ascribed to the fact that the antero-medial border of the tibia is largely subcutaneous throughout its whole length [5, 20].…”
Section: Discussionsupporting
confidence: 68%
“…The tibia and the fibula bones were the most frequently involved in open fractures making up about 45% of cases in this series. Several previous studies also reported similar findings [9, 16, 20, 21]. The reason for this observation has been ascribed to the fact that the antero-medial border of the tibia is largely subcutaneous throughout its whole length [5, 20].…”
Section: Discussionsupporting
confidence: 68%
“…Park et al [4] did not specify the percentages of superficial and deep infection. In the study of Sakaki et al [17] most infections were deep (10.71%), whereas, in the study of Kaftandziev et al…”
Section: Infection Ratementioning
confidence: 86%
“…Out of the 10 studies on intramedullary nailing as definitive management, only Tielinen et al [18] showed 0%. The other studies on intramedullary nailing presented less than 11% [4, 6, 10, 11, 16,17,19,[20][21][22], except for Sakaki et al [17], Park et al [4], and Kaftandziev et al [11] in which that rate was 17.85%, 22.0%, and 33.3%, respectively. Park et al [4] did not specify the percentages of superficial and deep infection.…”
Section: Infection Ratementioning
confidence: 98%
See 1 more Smart Citation
“…Das abordagens cirúrgicas, 78,5% foram realizadas nos membros inferiores e desses 65,5% na tíbia, a qual segundo Hungria et al (2013) 18 é o osso longo mais fraturado e que com maior frequência sofre fratura exposta.…”
Section: Albuquerque Et Al(2012)unclassified